Konsep Moderasi Beragama Dan Relevansinya Dengan Pendidikan Agama Islam Dalam Perspektif Pemikiran K.H. Abdurrahman Wahid - Muhammad Rahar Ardiyansyah; Fatkhurrohman Fatkhurrohman; Muhammad Saefullah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore the concepts of religious moderation and Islamic education according to the perspective of K.H Abdurrahman Wahid, and their relevance in the context of Indonesia's rich diversity. Conducted through qualitative literature research using content analysis approach, the study found that Abdurrahman Wahid views education as a process that should adapt to contemporary developments, integrating classical and modern knowledge without losing the essence of Islamic teachings. He advocates for stimulating intellectual development among students while avoiding doctrinal approaches. Furthermore, religious moderation in Indonesia is seen to have achieved a balanced approach, although efforts are needed to strengthen harmony amidst conflicts in various regions. Abdurrahman Wahid also highlights the relevance of Islamic education to religious moderation, emphasizing values such as multiculturalism, liberation, humanism, and inclusivity. The significance of these concepts is considered logical and crucial for discussion in the context of an era increasingly emphasizing openness over exclusivity.